COMPANY SIZE, CAPITAL INTENSITY, AND SALES GROWTH ON TAX AGGRESSIVITY - Putri, Julia; Anisa (The Asia Pacific Journal Of Management Studies, 2024)
This research aims to examine the influence of company size, capital intensity, sales growth on tax aggressiveness in Pharmaceutical subsector companies listed on the Indonesia Stock Exchange. This type of research is quantitative and the type of data used is secondary data, in the form of annual financial reports of pharmaceutical subsector companies for 2017-2022 obtained on the official website of the Indonesia Stock Exchange. namely as many as 30 companies. The samples were collected using a purposive sampling method and a research sample of 11 companies was obtained. This test was carried out using Eviews 9. From the results of simultaneous hypothesis testing (F test) company size, capital intensity and sales growth influence tax aggressiveness. Based on the results of the partial test (t test) company size, capital intensity and sales growth influence tax aggressiveness. Keywords: Company Size, Capital Intensity, Sales Growth, Tax Aggressiveness.